AJARAN KESUSILAAN DALAM GAGURITAN DHARMA PRAWERTI - Putu Sanjaya (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2017)
Gaguritan Prawerti Dharma is a literary work that contains the teachings of the Hindu religious morals namely Dasa Sila, Mala Tri, Tri Yadnya, Catur Prawerti, Catur Varna, Catur Paramitha, Sad Varga, Tri Parartha, and Daiwi and Asuri Sampad. The Hinduism contained in Gaguritan Prawerti Dharma teaches that every person should always make the moral teachings as a guide in any behavior that could be realized life in safety and peace. In addition Gaguritan Prawerti Dharma should teach humans which in this case is the Hindus, to be able to refrain from any wild desire. Gaguritan Dharma Prawerti containing Dharma teachings of morality really appropriate and relevant when used as a guideline for behavior. Current state of society who tend to behave the hedonistic, consumerist, materialistic, and pragmatic, if not matched by affirmation teachings of morality in every individual would bring the society to destruction and chaos. Thus why the moral teachings in life should always be upheld.